Tau oligomers impair memory and synaptic plasticity through the cellular prion protein - Claudia Balducci; Franca Orsini; Milica Cerovic; Marten Beeg; Beatrice Rocutto; Letizia Dacomo; Antonio Masone; Eleonora Busani; Ilaria Raimondi; Giada Lavigna; Po-Tao Chen; Susanna Leva; et al. (Acta Neuropathologica Communications)
Abstract Deposition of abnormally phosphorylated tau aggregates is a central event leading to neuronal dysfunction and death in Alzheimer’s disease (AD) and other tauopathies. Among tau aggregates, oligomers (TauOs) are considered the most toxic. AD brains show significant increase in TauOs compared to healthy controls, their concentration correlating with the severity of cognitive deficits and disease progression. In vitro and in vivo neuronal TauO exposure leads to synaptic and cognitive dysfunction, but their mechanisms of action are unclear. Evidence suggests that the cellular prion protein (PrPC) may act as a mediator of TauO neurotoxicity, as previously proposed for β-amyloid and α-synuclein oligomers. To investigate whether PrPC mediates TauO detrimental activities, we compared their effects on memory and synaptic plasticity in wild type (WT) and PrPC knockout (Prnp 0/0) mice. Intracerebroventricular injection of TauOs significantly impaired recognition memory in WT but not in Prnp 0/0 mice. Similarly, TauOs inhibited long-term potentiation in acute hippocampal slices from WT but not Prnp 0/0 mice. Surface plasmon resonance indicated a high-affinity binding between TauOs and PrPC with a K D of 20–50 nM. Immunofluorescence analysis of naïve and PrPC-overexpressing HEK293 cells exposed to TauOs showed a PrPC dose-dependent association of TauOs with cells over time, and their co-localization with PrPC on the plasma membrane and in intracellular compartments, suggesting PrPC-may play a role in TauO internalization. These findings support the concept that PrPC mediates the detrimental activities of TauOs through a direct interaction, suggesting that targeting this interaction might be a promising therapeutic strategy for AD and other tauopathies.